IEEE International Conference on Test, 2005.
DOI: 10.1109/test.2005.1584049
|View full text |Cite
|
Sign up to set email alerts
|

Technique to improve the performance of time-interleaved a-d converters

Abstract: Interleaving is one method of configuring a high-speed waveform digitizer. It is known that, in this method, using multiple A-D converters (ADC) enables sampling at a rate higher than the sampling rate of the ADC being used. Degradation of the dynamic range, however, results from such factors as phase error in the sampling clock applied to the ADC, and mismatched frequency characteristics among the individual ADCs. This paper describes a method for correcting these mismatches using a digital signal processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…We present here its frequency domain compensation method based on [6], [7]. We design and apply a digital filter for the timing skew compensation so that spurious due to the timing skew is cancelled.…”
Section: Proposed Timing Skew Compensation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We present here its frequency domain compensation method based on [6], [7]. We design and apply a digital filter for the timing skew compensation so that spurious due to the timing skew is cancelled.…”
Section: Proposed Timing Skew Compensation Methodsmentioning
confidence: 99%
“…The digital filter given by (6), (7) has the linear filter characteristics, and its group delay is τ.…”
Section: Propositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently lots of research has been reported for the calibration of the frequency response mismatch [5][6][7][8]. Most of these works are concerned with calibrating the channel mismatch by applying FIR type filters on each channel.…”
Section: Introductionmentioning
confidence: 99%
“…The author in [8] shows a method to compensate frequency-dependent mismatches based on a discrete Fourier transform (DFT). This approach is limited to a finite number of samples due to the DFT calculation and it is not shown how to extend this method to continuous processing of samples.…”
Section: Introductionmentioning
confidence: 99%